ECONOMIC EVALUATION OF SOME AGRICULTURAL INITIATIVE PROJECTS IN IRAQ - Barbaz & Al-Hiyali, Barbaz & Al-Hiyali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research aims to identify the economic and national feasibility of some agricultural activities benefiting from the agricultural initiative’s lending funds, as well as to show the impact of the agricultural initiative on these projects in terms of raising social profitability, in the light of the results of the national evaluation criteria addressed in the research. All the studied projects have achieved a net added value at the level of the national economy. The dairy cattle breeding project recorded the lowest net added value of about 914 million dinars (about 745 thousand dollars), and poultry projects achieved the highest added value of about 5 billion ID for the projects of table eggs production 4.9 billion ID for broiler projects, while the relative change in the standard showed that and the broiler production project is one of the most benefited from loan subsidies as the rate of change reached about 25%, while the project of broiler production and poultry hatchery and the project of raising milk cow have negative social return .The initiative’s subsidies have increased the social rate of return for these projects to around 24%, 20.5%, and 20%. Agricultural loans from the agricultural initiative raise the national profitability of agricultural projects, which would contribute to the process of agricultural development in Iraq.